Applying the mean-variance framework: portfolio optimization and comparative performance analysis in the emerging Colombian capital market - Jairo González-Bueno; Rima Tamošiūnienė; Camilo Gómez Morales; Gladys Rueda-Barrios (Business, Management and Economics Engineering)
Purpose – this paper adopts the mean-variance approach in optimizing portfolios within the Colombian capital market, a setting full of complications such as lack of liquidity and market concentration. It delivers actionable messages for emerging market stakeholders and formulates guidance aimed at enhancing risk-adjusted returns and informing portfolio management in markets with similar structural and economic conditions.